2021
DOI: 10.1016/j.isci.2021.102333
|View full text |Cite
|
Sign up to set email alerts
|

Diverse surface properties reveal that substratum roughness affects fungal spore binding

Abstract: Summary Binding to surfaces by fungal spores is a prerequisite to biofilm formation. The interactions of polytetrafluoroethylene (PTFE), glass, and silicon with three fungal spores, of differing shapes and sizes ( Aspergillus niger 1957, Aspergillus niger 1988, and Aureobasidium pullulans ), were investigated. A multifractal analysis was conducted to provide quantitative measures of density, dispersion, and clustering of spores on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Since the size of the surface features was in the nanometre range for the spin-coated surfaces, they were small relative to the cell, and hence the contact area between the cell and substrate may have been reduced and retention therefore reduced. In agreement with the lateral force results described here, work carried out on fungal spore retention on PTFE, glass and silicon surfaces found that A. niger 1957 attached in higher numbers to PTFE, which was the roughest surface [40]. However, it has also been shown that when A. niger spores were removed from AISI 304 stainless steel surfaces with different surface finishes and hence roughnesses (shot-treated or control), there was no significant effect on the cleanability of stainless steel.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Since the size of the surface features was in the nanometre range for the spin-coated surfaces, they were small relative to the cell, and hence the contact area between the cell and substrate may have been reduced and retention therefore reduced. In agreement with the lateral force results described here, work carried out on fungal spore retention on PTFE, glass and silicon surfaces found that A. niger 1957 attached in higher numbers to PTFE, which was the roughest surface [40]. However, it has also been shown that when A. niger spores were removed from AISI 304 stainless steel surfaces with different surface finishes and hence roughnesses (shot-treated or control), there was no significant effect on the cleanability of stainless steel.…”
Section: Discussionsupporting
confidence: 90%
“…[41]. Thus, for certain spores on specific surfaces, it would seem that the overall substratum surface roughness influenced spore binding rather than the physicochemical or chemical properties of the surfaces or spores [40]. However, this is clearly not the case for every scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A globose spore shape can reduce the surface area to volume ratio, thereby facilitating better survival for the organism (Bergman and Casadevall 2010, Wang and Lin 2012, Calhim et al 2018. Smooth spores or spores with simple ornamentation also allow for better wind dispersal (Diethart et al 2007, Dawson et al 2018 while the presence of spiny features on the spore surface can reduce contact, resulting in lower adherence (Whitehead et al 2021). For spore color, pigments produced by fungi protect species from environmental stressors such as UV (Horner et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important for ortho-k lenses, as these are worn overnight and less frequently replaced. As lenses age, scratches and deposit tend to accumulate, increasing attachment of microorganisms and rendering disinfection less effective [11,12]. In practice, this may be overcome with daily cleaning and regular enzymatic treatment.…”
Section: Introductionmentioning
confidence: 99%